Improving Product Quality through the Implementation of Good Manufacturing Practices and Vacuum Packaging in Smoked Catfish Businesses in Pasaman - Setiawan, Rizki Dwi; Ananda, Ananda; Sandy, Ikhlas Pratama; Juliyarsi, Indri; Melia, Sri; Vebriyanti, Ely; Sukma, Ade; Aulia, Surya; Putri, Annisa; Rifki, Adam Muhammad; Sari, Deta Yosfa; Salsabila, Andhini Aulia; Farid, Muhammad; Hasanah, Zahratul (Indonesian Journal of Community Services, 2025)
The production of smoked catfish in Pasaman Barat faces several challenges, including traditional smoking processes that lack the implementation of Good Manufacturing Practices (GMP), inadequate packaging and labeling, and limited marketing strategies. These conditions result in inconsistent product quality, a short shelf life, and low market competitiveness. This community service program aims to improve the product quality and sustainability of the Gusni Afrida MSME partner through the application of GMP, enhanced packaging techniques, and the development of digital marketing strategies.  The methods employed include training in GMP implementation, vacuum packaging techniques, labeling, replacement of equipment compliant with GMP standards, and mentoring in GMP applications. The program enhances the partner's understanding of GMP, vacuum packaging techniques, labeling, production management, and digital marketing, accompanied by the practical implementation of GMP. This involves the use of equipment that meets GMP standards, employing proper production personnel attributes, vacuum packaging techniques, and attractive product labeling. In addition, e-commerce-based marketing broadens market access.  Implementation of this program is expected to positively impact the quality, efficiency, and competitiveness of the partner's products. The adoption of GMP and modern marketing strategies can serve as models for the development of small businesses in the local food industry.